A systematic mapping review of outdoor activities and mobility in care homes - King, Amanda; Chadborn, Neil; Gordon, Adam L.; Logan, Phillipa A. (Wiley, 2016)
Background: Care home residents should be offered opportunities to participate in meaningful activities in an environment of their choice (National Institute for Health and Care Excellence, 2013). Whilst outdoor activities and mobility are believed to have health-related benefits, UK best practice recommendations are based on expert consensus. This research aimed to map the literature in this field and identify gaps in the evidence base.